Controller load balancing schemes in software defined networks - Selvi, Hakan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Software-de ned networking (SDN) has been proposed as a new networking paradigm which separates the control and data forwarding planes. The controllers which are centralized network control entities are crucial for meeting the performance and e ciency requirements of these systems. The placement of these network entities, switch assignment and their load-aware operation is a challenging research question. Although various load-balancing schemes are proposed in the literature, this research topic is yet to be explored adequately. In this thesis, we discuss load-balancing issues in SDN and propose a load-balancing scheme, namely Cooperative Load Balancing Scheme For Hierarchical SDN Controllers (COLBAS). Moreover, we evaluate the performance of this scheme and investigate important trade-o s.
Keywords: Software-defined networking (Computer network technology)